Ten Tales of Exceptional Entrepreneurship from Bangalore’s Software Miracle - Bannerjee, Moloy K; Banerjee, Siddharth; Sastry, P. Ranganath; Mittal , A.K. (Gyan Management Journal, 2015)
Entrepreneurship has become one of the globe’s most potent forces for transformation and an attractive career path in the space of a few short years. This book is based on interviews with ten pioneering entrepreneurs who carved a new path to establish successful start-ups in Bangalore, the technology capital oflndia.Start-up City is about Bangalore and its booming software sector. It looks at how ten successful firstgeneration entrepreneurs got to where they are, what they learned along the way and ultimately, why they chose Bangalore as their start-up city. In the process, it explores questions like: What makes successful entrepreneurs tick? Is it in their nature, or is it a function of how they were nurtured? What compels them to engage in unconventional, high-risk ventures? For anyone interested in Indian entrepreneurship, the struggles and eventual successes of these entrepreneurs will make for interesting and relevant reading. It will most benefit young and ambitious entrepreneurs who may be looking for inspirational. yet accessible, examples to follow on their own journeys.Authors Moloy K. Bannerjee, Siddharth Bannerjee and P. Ranganathan Sastry, who themselves have a wealth of experience in the software sector, private sector enterprises, social innovation and leadership, have chronicled the life of ten successful Indian software entrepreneurs, tracing how these individuals successfully navigated a new path in India.